PENGARUH VARIABEL STRUKTUR AKTIVA, RISIKO BISNIS, NET PROFIT MARGIN DAN FIRM SIZE TERHADAP STRUKTUR MODAL (Studi Pada Perusahaan Farmasi Yang Terdaftar Di BEI Periode 2008-2012) - Prasmitha Ayu Nelvistiarindah; Toto Rahardjo (Jurnal Ilmiah Mahasiswa FEB, 2013)
This research aims to determine that the asset structure variable, business risk, Net Profit Margin (NPM) and Firm Size (FS) affect the capital structure , either simultaneously or partial, and to determine which variables be the dominant influence on capital structure of the pharmaceutical company listed on the Indonesia Stock Exchange (IDX) the period of 2008 until 2012. This research belong to explanatory research. The research explains the relationship of independent variables and dependent variable. The object of research is the pharmaceutical company listed on the Stock Exchange from 2008 to 2012 . The samples used are 7 pharmaceutical company listed on the Stock Exchange and the method used was purposive sampling, that the determination of the sample with certain criteria. The analyze using multiple linear regression. The asset structure, business risk, NPM , FS has  negative effect on the capital structure by partial significantly of the pharmaceutical company listed on the Stock Exchange. The dominant variable to influence capital structure in pharmaceutical company listed on the Stock Exchange is asset  structure   Keywords : Capital structure, asset structure, business risk, the net profit margin and firm size